Improved the ability to read the Quran for slow learner students in Yogyakarta: Single case research approach - Hanif Cahyo Adi (Journal of Islamic Education and Innovation, 2021)
This study aims to improve the ability of slow learner students in reading  the Quran . This type of research is a single case or single-case research with the ABABA intervention model. The research subjects were student at Muhammadiyah Junior High School Kulonprogo Yogyakarta. The sampling technique used purposive sampling. The data were collected using an assessment sheet instrument based on practical tests, observation sheets, and interview protocols. The assessment data were analyzed using descriptive statistics in the form of scoring based on the results of the test or treatment given based on each stage. The enhancement of the subject's ability was carried out by the AIR (Auditory Intellectually Repetition) method which is has the banaficial category because in a short period it could give results even though it was not optimal. The AIR method itself is a learning model with assignments that emphasize understanding listening to the material with a practice that is carried out repeatedly to gain deep understanding. While the results of observations and interviews are described in a narrative. The results of the study concluded that there was an increase in the students' ability to read  the Quran  according to the observed aspects, namely the increase in the ability of the Makhorijul Huruf, Tawjid, and Tartil after attending the training. The ability of the subject's Makhorijul Huruf increased 66.6 % than before the intervention, they are from 30 to 50 as result. Tajwid ability increased 33.3 % from 30 to 40 as result, and Tartil ability increased by 14.28 % from 35 to 40 as resultr, and Tartib experienced an increase of 100 % from 25 to 50. These results indicate the increase in students' ability to read  the Quran in the quite good category.